Assessment of nasal carriage of staphylococcus aureus in patients with acne vulgaris - Demir, Betul; Denk, Affan; Erden, Ilker; Cicek, Demet; Ucak, Haydar (Turkish Soc Dermatology Venerology, 2015)
Background and Design: Systemic antibiotics, such as tetracycline and doxycycline are used in the treatment of inflammatory forms of moderate acne, or acne that is resistant to topical treatment. Oral isotretinoin treatment is the most effective treatment option in severe papulopustular and nodular forms of acne. Dose-related nasal carrier state of Staphylococcus aureus (S. aureus), has been reported in 90% of patients using isotretinoin. Long-term oral and/or topical antibiotic use in the treatment of acne causes changes in antibiotic susceptibility and emergence of methicillin-resistant S. aureus (MRSA) pathogens. The present retrospective study examined the colonization rates of S. aureus in patients who had an increase in acneiform lesions while taking medications for the treatment of acne and whose nasal swap samples were obtained and also investigated their relationship with treatment options. Materials and Methods: A total of 86 patients with moderate acne who attended our dermatology outpatient clinic with the complaints of acne and in whom nasal swap samples were obtained due to increased pustules during acne therapy. The patients were divided into three groups according to the treatment methods as patients receiving topical treatment, patients treated with oral doxycycline, and patients treated with oral isotretinoin. The results of the cultures were evaluated in three groups: no growth, methicillin-sensitive S. aureus (MSSA), and MRSA-isolated. Results: 39.5% culture positivity (S. aureus) were determined in 34 patients. Thirty two (94.1%) culture positivity were MSSA, and 2 (5.9%) culture positivity were MRSA. Twenty nine (58%) culture positivity were found in the patients using the oral isotretinoin. There was statistically significant culture positivity in the patients using oral isotretinoin compared to patients receiving other treatments (p<0.001). Conclusion: We observed that S. aureus colonization increased in patients using systemic isotretinoin independent from the drug dose and duration of drug use. There was no significant change in patients using systemic doxycycline and the colonization decreased in patients using topical antibiotic treatment.
Akne vulgarisli hastalarda nazal staphylococcus aureus taşiyicili?inin de?erlendirilmesi
Keywords: Acne vulgaris; staphylococcus aureus; nasal carriage